Hotel environmental sustainability practices within Institutional Theory Framework - Corina, Joseph; Esmie, Obrin Nichol; Chan, Valerie Sue Lin Abdullah; Patricia, Melvin Jussem (Institute of Borneo Studies, UNIMAS, 2016)
The purpose of this paper is to explain factors influencing the environment sustainability practice (ESP) in a Sarawak based hotel using the isomorphism tenet. An explanatory case study was applied. A semistructured interview with the hotel personnel was conducted and the hotel website was analysed. The coercive isomorphism arises from the invitation by the National Resource Environmental Board (NREB) to participate in the Sarawak Chief Minister Award and compliance with the ASEAN Tourism Standard, an indication of legitimacy, to be socially acceptable. In terms of the mimetic isomorphism, Hotel A imitated the best practices of its peers in the same organizational field. Finally, normative isomorphism evidence was proven by professional networking via attendance in the environmental award presentation. The content analysis reveals that there is a low disclosure of sustainability information on the hotel’s website. This research contributes to the CSR literature in the hotel industry particularly in an emerging economy in terms of promoting the particpation in the Environmental Award competition and disclosure on the website.